2009
DOI: 10.1007/s10508-008-9441-y
|View full text |Cite
|
Sign up to set email alerts
|

Human Physique and Sexual Attractiveness in Men and Women: A New Zealand–U.S. Comparative Study

Abstract: Men and women living in New Zealand and California completed five studies regarding human physique and sexual attractiveness. In Studies 1-3, women rated images of male stimuli and, in Studies 4-5, men rated female stimuli. In Study 1, women in both countries rated mesomorphic (muscular) and average male somatotypes as most attractive, followed by ectomorphic (slim) and endomorphic (heavily built) figures. In Study 2, amount and distribution of masculine trunk hair (chest and abdominal) was altered progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 45 publications
6
46
0
1
Order By: Relevance
“…Indeed, several studies have shown a significant association between country and WHR preference. For instance, in New Zealand a ratio of 0.7 was evaluated as the most sexually attractive (Dixson, Dixson, Bishop, & Parish, 2009), while in California as well as in China, preference was given to 0.6 (Dixson, Dixson, Li, & Anderson, 2007;Dixson et al 2010). In another investigation (Swami, Caprario, Tovée, & Furnham, 2006) carried out in industrialized societies (e.g.…”
Section: Cultural Influencesmentioning
confidence: 99%
“…Indeed, several studies have shown a significant association between country and WHR preference. For instance, in New Zealand a ratio of 0.7 was evaluated as the most sexually attractive (Dixson, Dixson, Bishop, & Parish, 2009), while in California as well as in China, preference was given to 0.6 (Dixson, Dixson, Li, & Anderson, 2007;Dixson et al 2010). In another investigation (Swami, Caprario, Tovée, & Furnham, 2006) carried out in industrialized societies (e.g.…”
Section: Cultural Influencesmentioning
confidence: 99%
“…The only scientific studies to attempt to test experimentally whether flaccid penis length affects male attractiveness asked women to rate five images created by modifying a single drawing of a male figure so that the test figures differed only in penis length (30)(31)(32). These important studies were not designed to quantify directly the relative effect of penis length on attractiveness compared with other sexually selected male traits, such as height and body shape (30)(31)(32).…”
mentioning
confidence: 99%
“…These important studies were not designed to quantify directly the relative effect of penis length on attractiveness compared with other sexually selected male traits, such as height and body shape (30)(31)(32). Therefore, it is still unknown whether penis size affects attractiveness when there is substantive variation in other, arguably more important, body traits, or whether interactions between these traits and penis size determine net attractiveness.…”
mentioning
confidence: 99%
“…A likely explanation is that a longer penis would more easily stimulate the cervix and the proximal vagina. In fact, a larger penis could be a fitness-related attribute, as a moderately larger penis has been cross-culturally associated with higher physical attractiveness of males as judged by women (Dixson, Dixson, Bishop, & Parish, 2010;Dixson, Dixson, Li, & Anderson, 2007;Dixson, Dixson, Morgan, & Anderson, 2007). Greater vaginal distention (that would be caused by penile pressure) increases vaginal electrical activity and muscle contractility leading to greater arousal (Shafik, El Sibai, Shafik, Ahmed, & Mostafa, 2004).…”
Section: Anatomical and Physiological Differences Between Vagina Cermentioning
confidence: 99%